Strategi Komunikasi Penyampaikan Informasi Iklim Stasiun Klimatologi Sampali Medan Dalam Upaya Meminimalkan Kegagalan Panen Padi Sawah Akibat Iklim Ekstrim - Siti Chodijah (Persepsi: Communication Journal, 2018)
The aims of this research are to describe the steps which must be done by Climatology Station of Sampali Medan so as the climate information to efforts minimize the harvest failure as effect extreme climate in district of Serdang Bedagai can be received and understood to farmers. This research uses descriptive qualitative research, the research that describe or depict the object under researched based on the facts on the ground regarding communication strategy of submission climate information at Climatology Station of Sampali Medan to efforts minimize the harvest failure rice paddy as effect extreme climate in District of Serdang Bedagai. Data were collected through interviews, and documentation. The location of this research at Climatology Station of Sampali Medan and in District of Serdang Bedagai. This research was conducted in February 2015 until August 2016. The results of this research that submission climate which is conducted by Climatology Station of Sampali Medan through electronic accepted to the farmers, so that the farmers understood and understanding about that submission climate the harvest failure effect extreme climate can be minimized.